Social workers' desk reference - Roberts, Albert R.; Greene, Gilbert J. (Oxford ; New York : Oxford University Press, 2002)
"Equally useful for students, teachers, and practitioners, the Social Workers' Desk Reference provides comprehensive information on all of the various aspects of social work. Topics covered within the 146 chapters include crisis management, family therapy, treatment planning, disorders, case management, community services, and risk assessment. Each chapter concludes with a list of references or recommended readings. An excellent glossary and thorough indexes round out this practical volume. Authoritative and readable, this resource provides one-stop shopping for social work."--"The Best of the Best Reference Sources, " American Libraries, May 2003.
The context of social work practice -- Social work ethics and values -- Applications of treatment approaches in clinical social work -- Assessment in social work practice : knowledge and skills -- Working with couples and families -- Developing and implementing treatment plans with specific groups and disorders -- Guidelines for specific techniques, interventions, and approaches -- Case management guidelines -- Community practices -- Working with vulnerable populations and persons at risk -- Social work and psychopharmacology -- Forensic social work -- Practice evaluation, outcome measures, and research -- Preparing for the future through visionary perspectives.
Includes bibliographical references and index.
Keywords: Social service -- Handbooks, manuals, etc; Handbooks; Service social -- Guides, manuels, etc; Collection "Travail social.".; Travailleur social; 2